The Eclipse of the 'Abbasid caliphate;: original chronicles of the fourth Islamic century - Amedroz, Henry Frederick; Margoliouth, D. S. (The 'Abbasid caliphate., 1920)
vol. I-II. The concluding portion of The experiences of the nations, by Miskawaihi ... Arabic text, edited by H. F. Amedroz: I. Reigns of Muqtadir, Qahir and Radi. II. Reigns of Muttaqi, Mustakfi, MutiŁ and TaiŁ. 1920-21.